ORANG MADURA: SUATU TINJAUAN ANTROPOLOGIS - Rochana, Totok (Humanus, 2012)
Ecologically, Madura Island has dry ecotype in a tropical weather, limy land, low rainfall, and low soil productivity. This condition contributes to shaping Maduraneses’ unique characters, not only in social relations but also moral economy. The Madura habitation pattern of tanean lanjang is a form of social unit creating self-confident individuals and community relations based on individualistic spirit. Ecological limitations makes Maduraneses trust not land ethics but labour ethics. The individualistic and self-confident characters result in Madura’s social and moral economic relations with simple, hardworking, deligent, thrifty, and religious individuals. Key words: dry ecotype, habitation pattern, social relations, moral economy